Moving toward more inclusive, affirming, and health-promoting nutrition education - Benes, Sarah; and Burtnyk, Erin (Journal of Physical Education, Recreation & Dance, 2025)
Nutrition units are a staple in many health education courses. While nutrition units can support the acquisition of critical functional knowledge and the development of important skills, there is also the potential for harm and the potential to perpetuate beliefs, ideas, and norms that can lead to disordered eating, the development of unhealthy relationships with food, or shaming of self and others (e.g., fat shaming). The purpose of this article is to outline several factors that may influence how health educators think about and teach nutrition, as well as practical strategies for creating inclusive, affirming, and health-promoting nutrition units.
Keywords: dept.hms; peer-reviewed